The cost of healthy versus current diets in the Netherlands for households with a low, middle and high education. (December 2022) - Hoenink, Jody C.; Waterlander, Wilma; Vandevijvere, Stefanie; Beulens, Joline W.J.; Mackenbach, Joreintje D.
Abstract: The cost of food is an important driver of food choice and most evidence suggests that healthier diets are more costly than less healthy diets. However, current attempts to model the cost of healthy and current diets do not take into account the variation in diets or food prices. We calculated the differential cost between healthy and current diets for households with a low, medium and high education in the Netherlands using the DIETCOST program. The DIETCOST program accounts for variations in dietary patterns and allows for the calculation of the distribution of the cost of bi-weekly healthy and current household diets. Data from the Dutch National Food Consumption Survey 2012–2016 was used to construct commonly consumed food lists for the population as a whole and for households with a low, medium and high education and linked to a local food price database. The average cost of current household diets was €211/fortnight (SD 8.9) and the healthy household diet was on average €50 (24%) more expensive. For households with a low, medium and high education, healthy diets were on average 10% (€17), 26% (€50) and 36% (€72) more expensive compared to current diets, respectively. All healthy diets could be classified as affordable (i.e. requiring less than 30% of the average disposable income) as diets required around 20% of the income. To conclude, while healthy diets were found to be affordable, we found that these were more expensive than current diets, especially for those with a higher educational level. This suggests that individuals will need to spend more money on food if they aim to adhere to dietary guidelines under the assumption that they will minimally adjust their diet. Bridging the gap between the cost of healthy and less healthy foods could be an important strategy for improving population diets. Highlights: Price of healthy and current Dutch diets were calculated using the DIETCOST program. DIETCOST program accounts for variations in dietary patterns. Cost of healthy fortnightly diet was €50 (24%) more expensive than current diet. Difference in cost increases by increasing household educational level.